Education - Wu, Kin Bing (World Bank, Washington, DC, 2012)
In the aftermath of the Wenchuan earthquake, measures to restore education will be a critical part of the recovery efforts in Sichuan province. The education system can play an important role in both: (i) minimizing the impact of the disaster on children; and (ii) improving disaster preparedness. To help restore normalcy for children and provide them with physical and psychological assistance after such a traumatic experience, restarting schools as quickly as possible is an immediate priority. To help strengthen disaster preparedness and management, a number of measures can be undertaken, such as rebuilding better school infrastructure and integrating school safety programs into the education curriculum. This note will review international experience in using the education sector to pursue the dual objectives of promoting short-term recovery and ensuring better disaster preparedness over the medium term. In particular, the note draws upon examples from the countries of India, Iran, and Japan, which have all experienced devastating earthquakes in recent years that have resulted in loss of life and extensive damage to school infrastructure in the affected areas. In all three countries, swift actions were taken in the education sector to assist students and rebuild schools, offering useful examples that China may wish to consider in shaping its own earthquake recovery efforts going forward.